Effectiveness of different dietary strategies in the management of obesity and obesity-related comorbidities - Małgorzata Jamka (Journal of Medical Science, 2021)
The prevalence of obesity has been increasing worldwide; however, the optimal dietary strategy for improving anthropometric and cardiometabolic parameters remains unknown. This review discusses the effectiveness of popular diets in the management of obesity and obesity-related comorbidities. The differences among popular diets are small and associated with dietary adherence and caloric intake. The Mediterranean diet is most effective in facilitating weight loss and improving cardiometabolic parameters, although the Central European diet seems to be a good alternative.